2001
DOI: 10.1046/j.1523-1755.2001.0590062104.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular cell number in normal subjects and in type 1 diabetic patients

Abstract: The essentially constant glomerular cell density in nondiabetic and diabetic subjects under different circumstances possibly indicates an underlying propensity for the glomerulus to regulate its architecture to maintain a constant number of cells per volume, no matter the size of the glomerulus or the severity of diabetic nephropathy studied in this set of patients. The reductions in podocyte numbers in both younger and older diabetic patients indicate a significant risk for functional abnormalities as diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 0 publications
3
74
0
4
Order By: Relevance
“…Previous studies have demonstrated that the decrease in podocyte number is a critical determinant contributing to the development of glomerulosclerosis in diabetic and non-diabetic glomerular diseases [3, 20, 21]. In the current study we show that podocytes detaching from the glomerular basement membrane and shed into the urinary space in experimental diabetic nephropathy adhere to tissue culture plates ex vivo, proliferate, and undergo morphological changes.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have demonstrated that the decrease in podocyte number is a critical determinant contributing to the development of glomerulosclerosis in diabetic and non-diabetic glomerular diseases [3, 20, 21]. In the current study we show that podocytes detaching from the glomerular basement membrane and shed into the urinary space in experimental diabetic nephropathy adhere to tissue culture plates ex vivo, proliferate, and undergo morphological changes.…”
Section: Discussionsupporting
confidence: 65%
“…Sclerosing glomeruli are characterized by progressive depletion of podocytes, resulting in denuded glomerular basement membrane areas and tuft adhesions, which may be considered as initial lesions of irreversible glomerular injury (4,7). Indeed, recent studies demonstrate that podocyte numbers are reduced early in glomeruli of diabetic patients with nephropathy (8,9). We have shown that TGF-␤1 induces apoptosis in podocytes in vitro and in vivo via a p38 MAPK and caspase-dependent mechanism.…”
mentioning
confidence: 80%
“…For this study 1.55 was used for β as previously described [13, 16]. Similar to the disector/fractionator method, images were obtained 5 µm apart from throughout each glomerulus, resulting in 13–19 sections per glomerulus.…”
Section: Methodsmentioning
confidence: 99%
“…Pagtalunan et al [2] used this method to count podocytes in diabetic Pima Indians. Since that publication, several other groups have used the Weibel-Gomez method to count the number of glomerular cells in patients with diabetes and other kidney diseases [14,15,16,17]. The disector/fractionator is a method of counting particles within a three-dimensional space independent of particle shape, size, or orientation [18,19,20].…”
Section: Introductionmentioning
confidence: 99%